The Impact of the interventionist policies of the western countries (France, Britain and the United States of America) in the Libyan crisis of 2011 - Chinembiri, G. (BUSE, 2019)
The research study examines the implications of the interventionist policies of Britain, France and USA through NATO in the Libyan crisis of 2011. The occurrence of the revolutionary movements of the 'Arab Spring' in early 2011 had a domino effect in Libya which led to peaceful protests and demonstrations against Gaddafi who was regarded as a dictator during his tenure in office. The US led military intervention which led to the ruthless murder of Gadhafi turned Libya into an anarchy, hence the study used the realism theoretical perspective to scrutinise the NATO intervention in the Libyan crisis of 2011. Hence, this also had an impact in Mali, Nigeria and Somalia where there was instability and insecurity as armed conflicts worsened in the aforementioned countries through illicit arms trafficking. This study used the descriptive research design in exploring the causes of instability and conflict in Libya after the intervention by NATO and the implications to that effect. Questionnaires, interviews and documentary reviews were used as data collection instruments in this research. Questionnaires were administered, interviews conducted to the targeted population in order to obtain relevant information pertaining to the military intervention in Libya and its implications in Libya and outside its borders. More so, the target population of the study were Libyan refugees and asylum seekers in Zimbabwe, UNHCR staff, academics and Western diplomatic staff members. The research gathered that the major intention of the Western countries and NATO intervention in Libya was premised on pursuing their national interest under the banner of the responsibility to protect. Hence, in future there is need for African countries to unite together in finding African solutions for African problems.
Keywords: Libyan crisis; revolutionary movements of the Arab Spring; NATO